Performance studies on co-gasification between coal/sawdust and coal/wood pellet using RSM - Mansur, F.Z. (Institute of Physics Publishing, 2020)
This work presents the comparative study between raw biomass and pre-treated biomass co-gasified with coal with the aimed to investigate the reliability of the pre-treated biomass to enhance the gasification performance. Sawdust and wood pellet (the pelletization form of sawdust) and blends of these two feedstocks with sub-bituminous coal, were gasified in an air atmosphere using an external heated fixed-bed downdraft gasifier system. Response surface methodology (RSM) incorporating with the central composite design (CCD) was applied to assist the comparison of all operating variables. The independent variables were investigated within the specific range of coal ratio from 25 to 75, gasification temperature from 650 to 850 Â°C and equivalence ratio from 0.20 to 0.30. Meanwhile, the dependent variables were evaluated on the H2/CO ratio in the syngas, higher heating value of the syngas (HHVsyngas) and gas yield (GY). The results revealed the H2/CO ratio in the syngas, HHVsyngas and GY of more than 1.585, 6.072 MJ/Nm3 and 2.464 Nm3/kg were achieved, respectively for both co-gasification. From the results, the H2/CO ratio in the syngas and GY from co-gasification of coal/wood pellet shows a higher value than that of the coal/sawdust. However, for the HHVsyngas, co-gasification of the coal/sawdust possess higher value with merely 1 difference from the coal/wood pellet. Therefore, co-gasified coal with wood pellet has the potential to be substitute with the sawdust. Â© Published under licence by IOP Publishing Ltd.